Pokdarwis' Efforts to Improve Community Tourism Promotion - Amini, Resa; Susanti, Reni; Fadri, Zainal; Dovick, Marteen (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2023)
The main problem in this thesis is that the Pokdarwis Sarasah Batangkughan has been implemented, but it is less effective in improving the community's economy through the development of the Sarasah Batangkughan nature tourism, lack of socialization to the community regarding the importance of managing existing natural potential in a better direction so as to produce added value to the community in the economic field in Nagari Salareh Aia, Palembayan District, Agam Regency. The type of research that the author uses is field research, using qualitative methods with a qualitative descriptive approach. Data collection techniques that the authors use are through observation, interviews and documentation. The data sources in this study were the Pokdarwis chairman, Pokdarwis vice chairman, Pokdarwis secretary, Wali Nagari Salareh Aia, Pokdarwis members, Nagari Salareh Aia community. Meanwhile, the data analysis technique used was data reduction, data presentation and drawing conclusions and to check the validity of the data, the researchers used source triangulation. The results of the research that the author conducted at the Pokdarwis Sarasah Batangkughan in an effort to increase the promotion of community tourism in Nagari Salareh Aia, namely in the form of prohibited fish activities, making people aware of the natural tourism potential of Sarasah Batangkughan, running the Pokdarwis Sarasah Batangkughan program, establishing community business land. The handling of problems carried out by the Pokdarwis Sarasah Batangkughan in increasing the promotion of community tourism in Nagari Salareh Aia, namely through deliberations, annual meetings, planning meetings and Pokdarwis evaluation meetings in Nagari Salareh Aia, Palembayan District, Agam Regency. The efforts of the Pokdarwis Sarasah Batangkughan in increasing the promotion of community tourism in Nagari Salareh Aia, so far have been carried out, but are less effective due to a lack of inadequate Human Resources (HR) in the field of tourism, lack of socialization to the community in order to gain understanding, so that the community has not ready to manage existing tourism in a better direction.